Resilience and Economic Intelligence through Digitalization and Big Data Analytics - Alina Mihaela Dima (Amfiteatru Economic)
The concept of “resilience” has gained popularity during the COVID-19 pandemic, especially from the perspective of networking of issues that had mostly been treated separately before. It has become clear that the interconnected systems of economy, environment and society need consistent and solid approaches for building resilience to similar shocks, thus avoiding cascading and widespread failure. The digital transformation process has been accelerated and it proved to be the lifeline for many businesses and public systems. However, digitalization exacerbated the social divide and put pressure on the companies that did not have the resources to face the challenges of new technology integration. The onlife digitalization is the new phase of society digitalization where big data and smart algorithms based on artificial intelligence changed the decision process mechanism in the public and private sectors. During 2020, leaders found themselves at historic crossroads, taking decisions under remarkable pressures and uncertainties. However, new opportunities are available to shape the economic recovery, restore the health of the environment, develop sustainable business models, strengthen regional development, revitalize global cooperation, harness Industry 4.0, and redesign the social contracts, skills, and jobs.